The Effect of Supervision on The Effectiveness of The Public Health Program In Cimaung Village - Pandji Santosa (Journal of Governance, 2022)
This research is motivated by the ineffectiveness of the implementation of the Family Hope Program Case Study of Public Health in Cimaung Village, Cimaung District, Bandung Regency. Based on these problems, it can be formulated as follows "How Big is the Effect of Supervision on the Effectiveness of the Hope Family Program (Case Study of Community Health in Cimaung Village, Cimaung District, Bandung Regency)". Analysis of research problems using Supervision theory from William H. Newman in the form of dimensions of Preliminary Supervision (feedforward control), "concurrent control" (concurrent control), and Feedback Control (feedback control). As for effectiveness theory, the Gogginet all theory approach is used in Sumaryadi, namely Procedural, Objective/Results, Monitoring and evaluation. Based on these theories the researcher proposes the hypothesis "The magnitude of the Effect of Supervision on the Effectiveness of the Family Hope Program (Case Study of Public Health in Cimaung Village, Cimaung District, Bandung Regency) is determined by the dimensions of feedforward control, concurrent control, concurrent control, feedback control. The method used in this research is Explanatory Research method, while the source of data collection comes from primary data sources and secondary data sources, sample collection techniques for Social Service Officers, PKH Companion, and PKH Recipient researchers used simple random sampling. The data analysis technique used is Simple Linear Regression. Based on the results of data processing, the results of the study show that there is a positive and significant relationship between Supervision of the Effectiveness of the Harapan Families Program (Case Study of Community Health in Cimaung Village, Cimaung District, Bandung Regency). he hypothesis proposed in this study was empirically tested.